Lanthanide Ions Complexes of 2-(4-amino antipyrine )-L-Tryptophane (AAT): Preparation, Identification and Antimicrobial Assay - Abbas, Alya (Iraqi Journal of Science, 2025)
In this work, L-Triptophan was coupled with diazotized 4-aminoantipyrine to give novel Mono azo ligand 2-(4-aminoantipyren)-L-Tryptophane (AAT). This prepared ligand was coordinated with chloride salts of [Ln=La(III), Ce(III), Nd(III), Eu(III) and Gd(III)] ions. The structural feature of the ligand and it’s metal complexes were identified by elemental analysis FTIR, HMMR, UV-Vis spectroscopy, magnetic susceptibility and molar conductivity. Chloride ion content was also appointed by Mohr method. The spectral data and physicochemical studies declares that the ligand act as neutral N,O-bidentat Pentagonal bipyramidal structure has been suggested for all prepared complexes which were exhibited (1:2) metal:ligand ratio at optimum condition as well as were formulated as [Ln(AAT)2Cl3]. The nature of all prepared Ln- complexes were performed after install the optimum pH and molar concentration that obeyed Lambert-Beer’s law over a concentration range of (2-4 10-4 M) at the maximum wave length (λmax). Furthermore the stability constant (K) and Gibbs free energy (ΔG) have also been studied. The in vitro antibacterial and antifungal assay of all prepared compounds have been evaluated.